2017
DOI: 10.3390/s17091936
|View full text |Cite
|
Sign up to set email alerts
|

A Biological Signal-Based Stress Monitoring Framework for Children Using Wearable Devices

Abstract: The safety of children has always been an important issue, and several studies have been conducted to determine the stress state of a child to ensure the safety. Audio signals and biological signals including heart rate are known to be effective for stress state detection. However, collecting those data requires specialized equipment, which is not appropriate for the constant monitoring of children, and advanced data analysis is required for accurate detection. In this regard, we propose a stress state detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In addition to health promotion, these devices are also being tested to identify and diagnose medical conditions, including detection of falls 6 , mental status 7 , heart disease 8 , neurological diseases 9 and others.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to health promotion, these devices are also being tested to identify and diagnose medical conditions, including detection of falls 6 , mental status 7 , heart disease 8 , neurological diseases 9 and others.…”
Section: Introductionmentioning
confidence: 99%
“…Sensors, in combination with machine learning algorithms, have been explored in an increasing variety of applications. For example, they have been shown to validly identify periods of high stress in some samples, to accurately recognize types of physical activities, and to be potentially useful for identifying episodes of anxiety and depression in youth 43–46 . Wearable physiological and other sensors are relatively new to pediatric research, however, and feasibility and acceptability data are somewhat scant.…”
Section: Discussionmentioning
confidence: 99%
“…to be potentially useful for identifying episodes of anxiety and depression in youth. [43][44][45][46] Wearable physiological and other sensors are relatively new to pediatric research, however, and feasibility and acceptability data are somewhat scant. In the current study, most youth with migraine rated the study methods involving sensors to be acceptable and generally low burden.…”
Section: Range Of Responsesmentioning
confidence: 99%
“…The authors found that the most distinctive features for detecting stress are EDA and HR. Remote monitoring of child safety through stress patterns was tackled in [ 83 ]. Detecting stress and anxiety in children with autism spectrum disorder (ASD) was investigated in [ 58 ].…”
Section: Wearable Devices and Machine Learningmentioning
confidence: 99%